Vprašanje zakonite uporabe termovizijske naprave v kazenskem postopku - Križnar, Primož (Pravnik, 2017)
Proactive response to crime is nowadays associated with the use of the advanced technology that allows law enforcement authorities to effectively monitor, prevent criminal activities and obtain evidence in favour of criminal indictment. Such pre-investigation is mostly directed against individuals who are potentially engaged in the acquisition and resale of illicit substances, among which the first place in popularity on the market still occupies cannabis with a high content of tetrahydrocannabinol (THC) and its variants. In pretrial procedures, the content of the data obtained by a thermal imaging device can can be an indication for the police that the observed premises are being used for illegal production of this (still) prohibited substance. However, on the battlefields of privacy the question is raised on the legality of thermal imaging devices used in connection with cannabis cultivation.
Keywords: kazenski postopek; kazensko procesno pravo; termovizijske naprave